PENGEMBANGAN LATIHAN VARIASI ZIG ZAG RUN TERHADAP KELINCAHAN ATLET KARATE KUMITE PENGCAB KKI LAMPUNG UTARA - Hikmah, Nur; Widia Ningrum, Asri; Trikandi, Sonya (Fakultas Ilmu Keolahragaan Unimed, 2024)
The aim of the research in this study was to add variations to zig-zag run training on the agility of Pengcab KKI North Lampung kumite karate athletes. The research uses the R n D method (Research and Development), researchers developed existing agility training products and then modified them again according to needs. Of the four development steps, researchers limited only two steps to collecting information and planning zig zag run training products at Pengcab KKI North Lampung. This research uses data collection techniques, namely literature review this means that the researcher looks for several theoretical sources related to the research. The results of research on the development of zig zag run training in gathering information contained several problems including lack of targeted training, lack of training program structure, training focused heavily on other aspects of physical training, and lack of variety in agility training. Product planning includes a variety of structured exercises with zig zag exercises using cone, variation of the zig zag run exercise by circling cone, and variations of the zig zag run exercise with running sprint forward and run sideways past cone